Retrieval algorithms of sea surface wind fields by TerraSAR-X image - Ren, Yongzheng; Lehner, Susanne; Brusch, Stephan; He, Ming Xia (European Space Agency (Special Publication) ESA SP, 2010)
TerraSAR-X is an operational satellite, which is equipped with X-Band synthetic aperture radar (SAR) with the characteristics of multi polarizations, high special resolution and along-track interferometric operation mode. So far only the TerraSAR-X images products of observation to the earth can be provided. This paper develops a retrieval algorithm of sea surface wind fields (SSW) by TerraSAR-X image. The Masuko model (1986) is validated with SIR-C/X-SAR NRCS and ECMWF ERA-40 data and found that there is an obvious system error. Based on this, a linear X-band VV polarization retrieval algorithm (XMOD) is developed. The correlation coefficient and RMS between the simulated NRCS by XMOD and SIR-C/X-SAR NRCS are 0.91 and 2.68dB respectively. The correlation coefficient and RMS between the simulated NRCS by XMOD and TerraSAR-X NRCS are 0.89 and 2.74dB respectively. XMOD is applied to the retrieval of SSW by the VV polarization TerraSAR-X images with different spatial resolutions. Compared with QuickScat SSW, the correlation coefficient and the RMS are 0.71 and 2.33 m/s respectively.
CRIS-Team Scopus Importer:2024-03-18
Keywords: NRCS; TerraSAR-X; Wind field; XMOD